Incidence of choledocholithiasis in gallstone disease - Tamrakar, Kishor Kumar; Bhattarai, Abhishek; Devakota, Pragya (Journal of Chitwan Medical College, 2018)
Background: Five to 20% patients with cholelithiasis also have choledocholithiasis. Most of them are diagnosed during a routine preoperative examination. Objective: To study the incidence of choledocholithiasis in patients with gallstone disease. Materials and methods: This is a retrospective observational study, conducted over a period of five years from January 2009 December 2013. Hospital record of the patients with a diagnosis of gallstone disease were evaluated. Clinical pictures of the disease and incidence of choledocholithiasis in those patients were analyzed. Result: One thousand four hundred sixty were diagnosed as a gallstone disease over a period of five years. Bile duct stone was found in 59 (4.04%) patients. The median age of presentation was 55 years. Classical charcots traid was seen in 9 (15.25%) patients. Ultrasound of the abdomen detected choledocholithiasis in 44 (74.57%) patients. Fifty four (91.52%) patients were managed with open cholecystectomy and CBD exploration. Conclusion: Incidence of choledocholithiasis in patients with gallstone disease is 4.04%. Most of the choledocholithiasis were diagnosed by ultrasound of the abdomen. Even in the era of minimally invasive surgery, when facilities and technical expertise are not available choledocholithiasis has to be managed with open CBD exploration.